A Conceptual Framework for Critical Appraisal in Systematic Mixed Studies Reviews. (October 2019) - Hong, Quan Nha; Pluye, Pierre
The past decade has been rich with methodological advancements in systematic reviews, several of which were inspired by the literature on mixed methods research. Systematic mixed studies reviews—that is, reviews combining qualitative and quantitative evidence—are increasingly popular as they can provide a better understanding of complex phenomena and interventions. However, they raise new challenges, especially regarding how to perform critical appraisal of the included studies that vary regarding the methodologies used. To address this challenge, conceptually clarifying critical appraisal is necessary. To this end, this article provides a framework for critical appraisal in systematic mixed studies reviews. This framework is an essential first step toward providing clear guidance on how to perform critical appraisal.